Extracorporeal photopheresis to attenuate decline in lung function due to refractory obstructive allograft dysfunction. Issue 4 (5th May 2021) - ,; Hage, Chadi A.; Klesney‐Tait, Julia; Wille, Keith; Arcasoy, Selim; Yung, Gordon; Hertz, Marshall; Chan, Kevin M.; Morrell, Matt; Goldberg, Hilary; Vedantham, Suresh; Derfler, Mary Clare; et al.
Abstract: Background: This study was designed to prospectively evaluate the efficacy of extracorporeal photopheresis (ECP) to attenuate the rate of decline of FEV1 in lung transplant recipients with refractory bronchiolitis obliterans. Due to an observed higher than expected early mortality, a preliminary analysis was performed. Study Design and Methods: Subjects from 10 lung transplant centres were assigned to ECP treatment or to observation based on spirometric criteria, with potential crossover for those under observation. The primary endpoint of this study was to assess response to ECP (i.e., greater than a 50% decrease in the rate of FEV1 decline) before and 6 months after initiation of ECP. Mortality was also evaluated 6 and 12 months after enrolment as a secondary endpoint. Results: Of 44 enrolled subjects, 31 were assigned to ECP treatment while 13 were initially assigned to observation on a non‐random basis using specific spirometric inclusion criteria (seven of the observation patients subsequently crossed over to receive ECP). Of evaluable patients, 95% of patients initially assigned to treatment responded to ECP with rates of FEV1 decline that were reduced by 93% in evaluable ECP‐treated patients. Mortality rates (percentages) at 6 and 12 months after enrolment was 32% and 41%, respectively. The most common (92%) primary cause of death was respiratory or graft failure. Significantly ( p  = 0.002) higher rates of FEV1 decline were observed in the non‐survivors (−212 ± 177 ml/month) when compared to the survivors (−95 ± 117 ml/month) 12 months after enrolment. In addition, 18 patients with bronchiolitis obliterans syndrome (BOS) diagnosis within 6 months of enrolment had lost 38% of their baseline lung function at BOS diagnosis and 50% of their lung function at enrolment. Conclusions: These analyses suggest that earlier detection and treatment of BOS should be considered to appreciate improved outcomes with ECP.